Capacity building and job productivity of library staff in selected universities in South-west Nigeria (2019)
The paper examined the level of capacity building to library staff in selected University Libraries; it identified the various forms of capacity building strategies put in place, and the extent to which capacity building affected-library job productivity. It also looked at the relationship between capacity building and job productivity in the selected universities in south-west of Nigeria. Survey research methodology was used with a total sample size of 202 library staff using the total enumeration sampling technique due to the small size of the population. Data was collected mainly through Questionnaire and analyzed using frequency distribution and regression analysis run on SPSS (2.0.) The result revealed that the level of capacity building for library staff was basically moderate with (20.5366) as it focused principally on job rotation and computer-based for library staff. The level of job productivity was high with (17.1905) therefore regular and targeted training programs should be organized periodically for library staff base on the identified-job requirements of each library staff which would lead to enhanced organizational productivity and staff job performance among other factors were part of the recommendations.